Building research culture and infrastructure - McRoy, Ruth G.; Flanzer, Jerry P.; Zlotnik, Joan Levy. (New York ; Oxford : Oxford University Press, 2012)
Drawing on the extensive experience of the authors, this book provides a roadmap to building research capacity. It outlines specific leadership strategies that deans and directors can use to access federal research funds; incentivize interdisciplinary research; enhance mentorship relationships between senior and junior researchers; and more.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Social service -- Research; Social work education